Infusing Communication Skills into Financial Accounting Curriculum: A perspective from the Digital Era - Nuwan Lakmal Hettiarachchi, Nuwan Lakmal Hettiarachchi; Tamil Selvan Subramaniam, Tamil Selvan Subramaniam; Sarala Thulasi Palpanadan, Sarala Thulasi Palpanadan; Anas Al-Fattal, Anas Al-Fattal (2023)
This study investigates financial accounting students’ attitudes about several aspects related to modern pedagogies focusing on communication skills development. The paper focuses on areas of students’ need to develop communication skills irrespective of cultural diversity and gender inequality, quiz-based learning, requirements, and assessment. The study employed an online survey of students at one of the largest business colleges in the Sultanate of Oman. The study surveyed 96 currently registered students to cover the research objectives and questions. The findings showed that the students enjoyed a high level of awareness of the importance and relevance of communication skills in relation to future employability. Students believed developing communication importance was not limited to careers in financial accounting as it was also extended to other careers requiring a post-secondary degree. Quiz-based learning strategies were found to be relevant in improving communication skills. The results also highlighted adaptability as a main assessment criterion of communication skills. The study provided bases for higher education institutions in the Sultanate of Oman or other countries to empower the generalizability of the findings. Another possible research could replicate the investigation in other fields of study. This paper brings several implications for instructional practice and pedagogies, as well as for policies of instructional training and development. The study is original in its particular context and specific time during the COVID-19 pandemic as attitudes toward online technologies have been shifting paradigms.